Atomistic Study of Interactions between Intrinsic Kink Defects and Dislocations in Twin Boundaries of Nanotwinned Copper during Nanoindentation - Xiaowen Hu; Yushan Ni; Zhongli Zhang (Nanomaterials, 2020)
In order to study the effects of kink-like defects in twin boundaries on deformation mechanisms and interaction between dislocations and defects in twin boundaries under localized load, nanotwinned Cu with two defective twin (TDT) boundaries is compared with the nanotwinned Cu with two perfect twin (TPT) boundaries, and nanotwinned Cu with single defective twin (SDT) boundary and single perfect twin boundary by simulating spherical nanoindentations using molecular mechanics. The indenter force-depth and hardness-contact strain responses were analyzed. Results show that the existence of intrinsic defects in twin boundary could reduce the critical load and critical hardness of nanotwinned material. A quantitative parameter was first proposed to evaluate the degree of surface atom accumulation around the indenter during nanoindentation, and it can be inferred that the surface morphology in TDT changes more frequently than the surface morphologies in TPT and SDT. The atomistic configurations of incipient plastic structures of three different models were also analyzed. We found that the intrinsic defects in twin boundary will affect the incipient plastic structures. The formation of twinning partial slip on the defective twin boundary happens before the contact of the dislocation and twin boundary. The kink-like defects could introduce Frank partial dislocation to the twin boundary during interaction between dislocation and twin boundary, which was not detected on the perfect twin boundary. In addition, the area of twinning partial slips on the upper twin boundary in the incipient plastic structures in SDT and TDT are larger than the twinning partial slip area in TPT, which results in the reduction of the critical hardness in SDT and TDT. The kink-like defects could also block the expansion of twinning partial slip on the twin boundary. Furthermore, we investigated the dislocation transmission processes in three different models. It is found that the dislocation transmission event could be delayed in model containing single defective twin boundary, while the transmission process could be advanced in model containing two consecutive defective twin boundaries. The quantitative analysis of dislocation length was also implemented. Result shows that the main emitted dislocation during nanoindentation is Shockley partial, and the dislocation nucleation in SDT and TDT is earlier than the dislocation nucleation in TPT due to the existence of defects. It is inferred that the intrinsic defects on twin boundaries could enhance the interaction between dislocations and twin boundaries, and could strongly change the structure evolution and promote the dislocation nucleation and emission. These findings about kink-like defects in twin boundaries show that the inherent kink-like defects play a crucial role in the deformation mechanisms and it should be taken into consideration in future investigations. Single defective twin boundary structure is recommended to delay the transmission and block the expansion of twin boundary migration. Some of the results are in good agreement with experiments.